Geografía Argentina y del mercosur Territorios y recursos de Brasil, Uruguay, Paraguay, Chile y Bolivia - BLANCO, Jorge (AIQUE, 2000)
CONTENIDO :COMUNICACIONES; POLIMODAL; BRASIL; URUGUAY; PARAGUAY; CHILE; BOLIVIA; AIQUE